Design of UWB patch antenna with 5g lower band notch characteristics using ring shape resonator - Mahfuz, M. M. Hasan; Islam, Md. Rafiqul; Habaebi, Mohamed Hadi; Sakib, Nazmus; Abdul Malik, Norun; Hossain, A. K. M. Zakir (IEEE, 2021)
ASEAN countries have proposed fifth generation (5G) forums for 5G applications at a frequency of 4.5–5.5 GHz and band stop antenna for 5G lower band from 4.5 GHz to 5.5 GHz. One UWB antenna have been designed and proposed by using RT 5880 with partial grounding on rectangular patch and ring shape resonator (RSR) on the ground. A single band notched UWB antenna were designed for 5G lower band application by using a rectangular slot at the top of the radiating patch and by adding RSR on ground plane of UWB antenna. The VSWR, return loss, gain and 2-D radiation pattern, surface current, radiation efficiency as well as gain prove that the proposed antenna has excellent performance in notched band and entire UWB band bandwidth frequencies. Therefore, the proposed antenna is also an excellent candidate for lower band 5G wireless applications.